A supported employment workbook : using individual profiling and job matching - Leach, Steve (Jessica Kingsley, 2002)
A practical tool for all job developers, this workbook presents strategies based on real situations and includes example exercises throughout. It draws on Steve Leach's thirteen years' practical experience in supported employment and is based on the principle of developing a client-centred approach to job development. It emphasizes the central importance of self-determination - ensuring that the individual makes their own choices to determine their future career. This flexible guide shows ways in which a support strategy can be developed in partnership with both employee and employer. Chapters.